2008
DOI: 10.1093/jnci/djn134
|View full text |Cite
|
Sign up to set email alerts
|

Design and Endpoints of Clinical Trials in Hepatocellular Carcinoma

Abstract: The design of clinical trials in hepatocellular carcinoma (HCC) is complex because many patients have concurrent liver disease, which can confound the assessment of clinical benefit. There is an urgent need for high-quality trials in this disease. An expert panel was convened by the American Association for the Study of Liver Diseases to develop guidelines that provide a common framework for designing trials to facilitate comparability of results. According to these guidelines, randomized phase 2 trials with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
1,321
2
29

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,524 publications
(1,369 citation statements)
references
References 58 publications
17
1,321
2
29
Order By: Relevance
“…On the other hand, TACE and sorafenib are recommended for patients at different stages of the disease, and thus a direct comparison was not foreseen. (42,43) With this in mind, and recognizing the importance of a comprehensive understanding of updated efficacy and safety data of lipiodol TACE, we performed a systematic review of available clinical studies selected according to predefined inclusion/exclusion criteria and assessed according to a standardized methodology. Separate analyses were performed for efficacy and safety data.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, TACE and sorafenib are recommended for patients at different stages of the disease, and thus a direct comparison was not foreseen. (42,43) With this in mind, and recognizing the importance of a comprehensive understanding of updated efficacy and safety data of lipiodol TACE, we performed a systematic review of available clinical studies selected according to predefined inclusion/exclusion criteria and assessed according to a standardized methodology. Separate analyses were performed for efficacy and safety data.…”
Section: Discussionmentioning
confidence: 99%
“…These stages defined the BCLC staging system in the initial proposal, 6 which was prospectively validated by a number of later studies. [22][23][24][25] In addition to these prospective validations, several studies have demonstrated the ability of the model. 26,27 It has been recently endorsed by numerous groups 1,21,28 and is included in the guidelines for the management of HCC from the American Association for the Study of Liver Diseases.…”
Section: Formentioning
confidence: 99%
“…1). 7 Potentially curative treatments for HCC require surgical expertise; however, both hepatic resection and orthotopic liver transplantation require careful patient selection. Both modalities are limited in their practical implementation by the fact that most patients present with an advanced tumor burden.…”
Section: The Problemmentioning
confidence: 99%
“…29 More recently, changes in enhancement have been incorporated into assessing response to molecular therapeutics in the management of HCC. 7 If sorafenib does not cause tumor shrinkage, outside of unmanageable toxicity, the question of when to stop the drug becomes important. Typically the appearance of a new lesion would suggest clear progression.…”
Section: Monitoring Of Therapymentioning
confidence: 99%